System Administration Application on Orbit Perdana - Utama, Widyanto; Setiawan, Alexander; Setiabudi, Andy (Jurnal Infra, 2015)
Orbit Perdana store is a store that is engaged in the sale of household electronic goods. The process at this store is still done semi-manually, for order entry, ordering goods and stock recording is done manually. However, for the manufacture of goods price list is computerized. It can bring harm to the company, for example, for recording miscalculation could happen that could bring harm to the company, then on receipt of the order, which can not be faulted human memory is limited so that it can make a person forget, it can be disappointing customer so that the company valued less by the customer. Section while ordering goods, miscommunication can occur between the owner who ordered goods to the supplier, which could also bring losses for companies such as excessive stockpile goods.Based on the problems being faced, then the web-based application is administration system is designed to provide the results of the performance of the recording company orders, booking orders, and company reports.Based on the test results, this application can record company data, supplier, customer, stock of goods, accounts payable and receivable, sales returns and purchase, and reports.Â  Applications can also provide flexibility to the owner to be able to perform charging master data without having to go through the application directly